Answer:
The first thing that we need to do is subtract 4.5 from both sides because that would removed the 4.5 from the left side and leave us with m by itself. So we get the following
and that is our solution.
<u><em>Hope this helps! Let me know if you have any questions</em></u>
Multiply 2/3 by 84 which is 56.
11/50=1.1/5=0.22
They are indeed equivalent.
Answer:
The expressions are not equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(2)-6=-30
Step-by-step explanation:
Two expressions are said to be equal if after a number is substituted to the expression, they produce the same result (that is they have the same value).
To determine whether -3x(5-4)+3(x-6) is equivalent to -12x-6, we have to substitute the same number to the expression and see if it produces the same result.
Substituting 2 to the first expression gives:
-3×2(5-4) + 3(2 - 6) = -6 - 12 = -18
Substituting 2 to the second expression gives:
-12(2) - 6 = -24 - 6 = -30
Since -3×2(5-4) + 3(2 - 6) = -6 - 12 = -18 and -12(2) - 6 = -24 - 6 = -30, the expressions are not equivalent because they do not produce the same result.